2487. Vaccination Rates in Post-Transplant Hematopoietic Stem Cell Transplant (HSCT) Patients: Where Do We Stand?. (26th November 2018) - Ahmad, Hiba; Perreault, Sarah; McManus, Dayna; Foss, Francine; Isufi, Iris; Seropian, Stuart; Topal, Jeffrey
Abstract: Background: HSCT patients are at an increased risk of developing infections after transplant due to the loss of immunogenicity from prior vaccinations. Current national and international guidelines recommend routine revaccinations at a fixed dosing schedule for HSCT patients post-transplant. Although immunization adherence is vital to prevent infections, compliance with post-transplant vaccinations is unknown. The primary endpoint of this study was the completion rate of the post-transplant vaccination series. Secondary endpoints included identifying reasons for noncompliance, rates of breakthrough vaccine-preventable infections, and assessing post-vaccination antibody responses based on titers. Methods: A single-center, retrospective study of adult HSCT patients at Yale New Haven Hospital between January 2010 and September 2015 was performed. Patients were excluded if: <18 years of age, deceased prior to one year post-transplant, transferred care to an outside facility, or were lost to follow-up. Results: A total of 512 HSCT patients were evaluated. 390 (76%) patients were initiated on the vaccination series. Of the 390 patients, 275 (71%) patients were started at one year follow-up per institutional guidelines. The most common reasons for non-initiation or delayed initiation of the vaccine series included disease relapse (14%), active graft vs. host disease (9%), and the need for immunosuppressive therapy (5%). Of the patients initiated on the vaccination series, only 187 (48%) patients completed the entire vaccination series; with the majority of whom were autologous HSCT patients (72%). The most common reasons for an incomplete vaccination series included maintenance chemotherapy (19%), disease relapse (16%), and lost to follow-up (10%). Of the patients who completed the vaccination series, 19% had the appropriate post-vaccination titers obtained. Of the patients who received at least one or more doses of pneumococcal vaccine post-transplant, 8 patients (2%) developed a breakthrough infection with S. pneumoniae . Conclusion: This study adds important data to the limited body of literature on HSCT vaccine compliance rates. Future studies on the best interventions to improve compliance rates are warranted. Disclosures: All authors: No reported disclosures.